2020
DOI: 10.1038/s41467-020-17244-y
|View full text |Cite|
|
Sign up to set email alerts
|

Proton irradiation-decelerated intergranular corrosion of Ni-Cr alloys in molten salt

Abstract: The effects of ionizing radiation on materials often reduce to "bad news". Radiation damage usually leads to detrimental effects such as embrittlement, accelerated creep, phase instability, and radiation-altered corrosion. Here we report that proton irradiation decelerates intergranular corrosion of Ni-Cr alloys in molten fluoride salt at 650°C. We demonstrate this by showing that the depth of intergranular voids resulting from Cr leaching into the salt is reduced by proton irradiation alone. Interstitial defe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 30 publications
(35 reference statements)
0
39
0
Order By: Relevance
“…This mechanism is not likely relevant to molten salt because a protective oxide scale does not form. The previously mentioned study by Zhou et al [13] attributed irradiation decelerated corrosion of a Ni-Cl alloy in FLiNaK salt to a solid-state mechanisms in which irradiation-produced interstitials aided the migration of Ni to grain boundaries, resulting in a "self-healing" effect. Again, if this mechanism was active in the present experiment, there is no explanation for why it is not active in alloy N, other than concluding that the total attack in the alloy N samples were too low to show any significant effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism is not likely relevant to molten salt because a protective oxide scale does not form. The previously mentioned study by Zhou et al [13] attributed irradiation decelerated corrosion of a Ni-Cl alloy in FLiNaK salt to a solid-state mechanisms in which irradiation-produced interstitials aided the migration of Ni to grain boundaries, resulting in a "self-healing" effect. Again, if this mechanism was active in the present experiment, there is no explanation for why it is not active in alloy N, other than concluding that the total attack in the alloy N samples were too low to show any significant effects.…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al conducted experiments in which Ni-Cr alloys were exposed to FLiNaK salt while simultaneously irradiated with a proton beam, and found that irradiation decelerated corrosion of the alloy [13]. They attributed this deceleration to grain boundary self-healing due to the abundance of irradiation-produced interstitials in the irradiated alloy This paper reports the method and results of an experiment in which molten salt capsules were exposed to neutron irradiation to study the effect of radiation on material corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Another phenomenon that needs further experimental investigation is the effect of irradiation on corrosion. Recent studies have shown that proton irradiation decelerated intergranular corrosion of Ni-Cr alloys in molten salts [29]. It is unclear if neutron irradiation will have the same effect, but additional experiments are warranted.…”
Section: Corrosionmentioning
confidence: 99%
“…As one example of the importance of understanding the fundamental mechanisms of transport within GBs of alloys, consider recent experiments by Zhou et al that examined the corrosive behavior of Ni-Cr alloys in contact with FLiNaK molten salt [15]. They found that the salt preferentially attacks the GBs and, further, preferentially leaches out the Cr from the GBs.…”
Section: Introductionmentioning
confidence: 99%